Coronavirus disease of 2019 (COVID-19) facts and figures: What every dermatologist should know in this hour of need - Yashpal Manchanda; Sudip Das; Abhishek De (Wolters Kluwer Medknow Publications, 2020)
Coronavirus disease of 2019 (COVID-19) pandemic has affected India and world as a whole, like nothing in the recent history and we, dermatologists, are also affected directly or indirectly. In this review, we have tried to address all COVID-19-related information we need to be aware of as a health-care professional. We have discussed the relevant details of the disease: the agent, the symptomatology, common preventive measures, investigations, and management outline. We have also discussed the implications of COVID-19 in dermatology practice and given a basic guideline for dermatology practice during the pandemic